2018
DOI: 10.1002/eco.1943
|View full text |Cite
|
Sign up to set email alerts
|

Water use strategies for two dominant tree species in pure and mixed plantations of the semiarid Chinese Loess Plateau

Abstract: Understanding the water sources and physiological responses to soil moisture pulses for plantation species, particularly in mixed plantations, are essential to assess the water use strategy and vegetation restoration in semiarid regions. We used hydrogen stable isotopes in plant and soil water to determine the potential water sources for Pinus tabuliformis and Hippophae rhamnoides in both pure and mixed plantations in the semiarid Chinese Loess Plateau during the vigorous growing season (June–August) in 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 62 publications
1
22
1
2
Order By: Relevance
“…Plant physiological response is expected only when the rainfall amount promotes soil water status. Previous studies indicated that a small rainfall amount (e.g., 5 mm) was the lower threshold to stimulate plant activities (Tang et al., ; Zeppel et al., ;; Zhao & Liu, ). However, Thomey et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Plant physiological response is expected only when the rainfall amount promotes soil water status. Previous studies indicated that a small rainfall amount (e.g., 5 mm) was the lower threshold to stimulate plant activities (Tang et al., ; Zeppel et al., ;; Zhao & Liu, ). However, Thomey et al.…”
Section: Discussionmentioning
confidence: 96%
“…Plant physiological response is expected only when the rainfall amount promotes soil water status. Previous studies indicated that a small rainfall amount (e.g., 5 mm) was the lower threshold to stimulate plant activities (Tang et al, 2018;Zeppel et al, 2008;;Zhao & Liu, 2010). However, Thomey et al (2011) indicated that small rainfall events may only increase microbial respiration in shallow soil layers and could not trigger plan root activities in relative deeper soil layers.…”
Section: Rainfall Pulse Effect On Carbon Fluxesmentioning
confidence: 99%
“…In the northern region of the Loess Plateau, especially in the arid and semi-arid zones, efficient use of water resources is critical for sustainable plant growth. Plant water use strategy is controlled by many factors, including soil properties, water condition and functional plant root (Yu et al, 2015;Tang et al, 2018). The effect of soil texture and water conditions on the growth of A. pedunculata was analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, mycorrhizal fungal plant partners also contribute to water acquisition and transport, extending the soil volume explored by roots (Lehto and Zwiazek 2011). Thus, contrasted results in the literature make it impossible to conclude whether or not water uptake patterns correspond to the distribution of fine roots in woody species (Green and Clothier 1995;Midwood et al 1998;Liu et al 2011;Tang et al 2018).…”
Section: Introductionmentioning
confidence: 99%